Skip to content
GitLab
Explore
Sign in
Primary navigation
Search or go to…
Project
I
iris
Manage
Activity
Members
Labels
Plan
Wiki
Code
Merge requests
Repository
Branches
Commits
Tags
Repository graph
Compare revisions
Snippets
Build
Pipelines
Jobs
Pipeline schedules
Artifacts
Deploy
Releases
Model registry
Operate
Environments
Analyze
Value stream analytics
Contributor analytics
CI/CD analytics
Repository analytics
Model experiments
Help
Help
Support
GitLab documentation
Compare GitLab plans
Community forum
Contribute to GitLab
Provide feedback
Terms and privacy
Keyboard shortcuts
?
Snippets
Groups
Projects
Show more breadcrumbs
Paolo G. Giarrusso
iris
Commits
4f9deccf
Commit
4f9deccf
authored
7 years ago
by
Robbert Krebbers
Browse files
Options
Downloads
Patches
Plain Diff
Prove (P -∗ Q) ⊣⊢ ∃ R, R ∗ □ (P ∗ R → Q) and dually for →.
parent
066ce7e2
No related branches found
Branches containing commit
No related tags found
Tags containing commit
No related merge requests found
Changes
2
Hide whitespace changes
Inline
Side-by-side
Showing
2 changed files
theories/base_logic/derived.v
+18
-0
18 additions, 0 deletions
theories/base_logic/derived.v
theories/base_logic/lib/viewshifts.v
+3
-0
3 additions, 0 deletions
theories/base_logic/lib/viewshifts.v
with
21 additions
and
0 deletions
theories/base_logic/derived.v
+
18
−
0
View file @
4f9deccf
...
...
@@ -536,6 +536,24 @@ Proof. intros; rewrite -always_and_sep_r'; auto. Qed.
Lemma
always_laterN
n
P
:
□
▷^
n
P
⊣⊢
▷^
n
□
P
.
Proof
.
induction
n
as
[|
n
IH
];
simpl
;
auto
.
by
rewrite
always_later
IH
.
Qed
.
Lemma
wand_alt
P
Q
:
(
P
-∗
Q
)
⊣⊢
∃
R
,
R
∗
□
(
P
∗
R
→
Q
)
.
Proof
.
apply
(
anti_symm
(
⊢
))
.
-
rewrite
-
(
right_id
True
%
I
uPred_sep
(
P
-∗
Q
)
%
I
)
-
(
exist_intro
(
P
-∗
Q
)
%
I
)
.
apply
sep_mono_r
.
rewrite
-
always_pure
.
apply
always_mono
,
impl_intro_l
.
by
rewrite
wand_elim_r
right_id
.
-
apply
exist_elim
=>
R
.
apply
wand_intro_l
.
rewrite
assoc
-
always_and_sep_r'
.
by
rewrite
always_elim
impl_elim_r
.
Qed
.
Lemma
impl_alt
P
Q
:
(
P
→
Q
)
⊣⊢
∃
R
,
R
∧
□
(
P
∧
R
-∗
Q
)
.
Proof
.
apply
(
anti_symm
(
⊢
))
.
-
rewrite
-
(
right_id
True
%
I
uPred_and
(
P
→
Q
)
%
I
)
-
(
exist_intro
(
P
→
Q
)
%
I
)
.
apply
and_mono_r
.
rewrite
-
always_pure
.
apply
always_mono
,
wand_intro_l
.
by
rewrite
impl_elim_r
right_id
.
-
apply
exist_elim
=>
R
.
apply
impl_intro_l
.
rewrite
assoc
always_and_sep_r'
.
by
rewrite
always_elim
wand_elim_r
.
Qed
.
(* Later derived *)
Lemma
later_proper
P
Q
:
(
P
⊣⊢
Q
)
→
▷
P
⊣⊢
▷
Q
.
...
...
This diff is collapsed.
Click to expand it.
theories/base_logic/lib/viewshifts.v
+
3
−
0
View file @
4f9deccf
...
...
@@ -79,4 +79,7 @@ Qed.
Lemma
vs_alloc
N
P
:
▷
P
=
{
↑
N
}=>
inv
N
P
.
Proof
.
iIntros
"!# HP"
.
by
iApply
inv_alloc
.
Qed
.
Lemma
wand_fupd_alt
E1
E2
P
Q
:
(
P
=
{
E1
,
E2
}
=∗
Q
)
⊣⊢
∃
R
,
R
∗
(
P
∗
R
=
{
E1
,
E2
}=>
Q
)
.
Proof
.
rewrite
uPred
.
wand_alt
.
by
setoid_rewrite
<-
uPred
.
always_wand_impl
.
Qed
.
End
vs
.
This diff is collapsed.
Click to expand it.
Preview
0%
Loading
Try again
or
attach a new file
.
Cancel
You are about to add
0
people
to the discussion. Proceed with caution.
Finish editing this message first!
Save comment
Cancel
Please
register
or
sign in
to comment